A reading of the Qatari state’s trends from the Syrian crisis 2011 – 2018 - MUSSA, OUASSFI (Journal of Economic, Administrative and Legal Sciences, 2023)
This study aims to research and explore the role played by the Qatari regime in the Syrian conflict, and to clarify the reasons for this hostility by researching the nature of the Syrian-Qatari relations before the Syrian crisis in 2011. Which, to say the least, was at best, but the relationship between the Qatari Emir And President Bashar al-Assad was a family relationship, but things will take another turn after the Syrian rejection of the gas pipeline project from Qatar through Syrian territory to European territory. Syria, which has strong relations with the Russian regime and extends to the era of the Soviet Union, and which Russia owns the port of Tartus inside Syrian territory, cannot accept and accept such a request, which aims to stifle the Russian economy. This refusal cost the Syrian regime a lot, as the Qatari regime provided political support to the opposition in order to isolate the regime, as it instructed its media networks, led by Al-Jazeera, in order to distort the Syrian regime and venerate the opposition, in addition to the unlimited military support it provided to the military organizations operating on the Syrian arena. By purchasing various weapons and passing them through opposition-controlled areas.